An evaluation of the policy context on psychosocial risks and mental health in the workplace in the European Union: achievements, challenges, and the future - Leka, Stavroula; Jain, Aditya Kailash; Iavicoli, Sergio; Di Tecco, Cristina (Hindawi, 2015)
Despite the developments both in hard and soft law policies in the European Union in relation to mental health and psychosocial risks in the workplace, a review of these policies at EU level has not been conducted to identify strengths, weaknesses, and gaps to be addressed in the future. Keeping in mind that the aim should be to engage employers in good practice, ideally such policies should include key definitions and elements of the psychosocial risk management process, covering risk factors, mental health outcomes, risk assessment and preventive actions, or interventions. The current paper aims to fill this gap by reviewing hard and soft law policies on mental health in the workplace and psychosocial risks applicable at EU level and conducting a gap analysis according to a set of dimensions identified in models of good practice in this area. Our review of ninety-four policies in total revealed several gaps, especially in relation to binding in comparison to nonbinding policies. These are discussed in light of the context of policy-making in the EU, and recommendations are offered for future actions in this area.